Karakterisasi biokomposit sheep hydroxyapatite (sha)/shellac/tepung terigu - Izmi Mahfudi; Joko Triyono; Teguh Triyono (Universitas Sebelas Maret, 2018)
The development of science and technology has led to new inovations in the medical field, especially ortopedic. The aim of those inovations is to find the alternatives of good materials that can replace the broken sturcture of bone tissue. One of the innovations conducted is the characterization of sheep hydroxyapatite biocomposite. This study aims to investigate the mechanical properties of the material Sheep Hydroxyapatite (SHA) / shellac / wheat fluor. Sheep bone powder already gained from the crusher process and meshing into size of 100 and are soaked for 24 hours, then mixed with wheat flour with the ratio 30 : 70 %wt, 40 : 60 %wt, 50 : 50 %wt, 60 : 40 %wt, 70 : 30 %wt. The next step is the forming process and calcination at a temperature of 900oC with a increase of 10 °C/min. Results of X-Ray Diffraction (XRD) shows that the diffraction peak of SHA/shellac/wheat flour is the value of 2θ: 32.0747º, 33.1943º, 32.5338º. The lowest hardness number of SHA/shellac/wheat flour is 2.86 VHN and the highest is 14.80 VHN, also the highest strong pressure number is 0.20 MPa. The result of microscophy at observation using SEM shows Thar the SHA/shellac/wheat flour 50:50 % wt sample has more porosity as.